2012
DOI: 10.1186/gb-2012-13-1-r1
|View full text |Cite
|
Sign up to set email alerts
|

Genetic adaptation to high altitude in the Ethiopian highlands

Abstract: BackgroundGenomic analysis of high-altitude populations residing in the Andes and Tibet has revealed several candidate loci for involvement in high-altitude adaptation, a subset of which have also been shown to be associated with hemoglobin levels, including EPAS1, EGLN1, and PPARA, which play a role in the HIF-1 pathway. Here, we have extended this work to high- and low-altitude populations living in Ethiopia, for which we have measured hemoglobin levels. We genotyped the Illumina 1M SNP array and employed se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
208
3
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 371 publications
(222 citation statements)
references
References 40 publications
(82 reference statements)
9
208
3
2
Order By: Relevance
“…Gene variants associated with adaptation in this population include ARNT (encoding HIF-1β) and EDNRB. 112 Finally, in addition to studies conducted in humans residing at high altitude, recent work has also examined the genetics associated with development of HPH in cattle. Comparison between cattle that developed PH at altitude and those that did not revealed variants in EPAS1 that likely confer gain of function and were associated with HPH susceptibility.…”
Section: Mechanisms Of Hph: Lessons From High-altitude Genomicsmentioning
confidence: 99%
“…Gene variants associated with adaptation in this population include ARNT (encoding HIF-1β) and EDNRB. 112 Finally, in addition to studies conducted in humans residing at high altitude, recent work has also examined the genetics associated with development of HPH in cattle. Comparison between cattle that developed PH at altitude and those that did not revealed variants in EPAS1 that likely confer gain of function and were associated with HPH susceptibility.…”
Section: Mechanisms Of Hph: Lessons From High-altitude Genomicsmentioning
confidence: 99%
“…Such empirical studies also highlight the current deficiencies of such methods, as some of the best signals in these studies are not shared across populations with broadly similar environments and instead indicate that adaptation has occurred through independent mutations in the same gene or pathway. For example, high-altitude adaptation seems to have a different genetic basis in highland Ethiopian and Andean populations (Bigham et al 2010;Scheinfeldt et al 2012). Methods based on environmental correlations will fail to detect such cases, unless the data are split into the appropriate geographic subsets (e.g., Hancock et al 2011c) on an appropriate geographic scale (Ralph and Coop 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Candidate genes include basic HLH family member e41 (BHLHE41 also known as DEC2 or SHARP1), mitochondrial calcium uptake 1 (MICU, also known as CBARA1), vav 3 guanine nucleotide exchange factor (VAV3), arylhydrocarbon receptor nuclear translocator 2 (ARNT2), and thyroid hormone receptor b (THRB) as well as a generich region on chromosome 19 containing several genes that are involved in vascular physiology (CXCL17 and PAFAH1B3) or have been linked to hypoxia (LIPE) (Scheinfeldt et al 2012;Huerta-Sanchez et al 2013;Udpa et al 2014). Two genes in particular, ARNT2 and THRB, show suggestive relationships with hemoglobin concentration; for example, Ethiopian Amhara with two copies of the THRB rs826216 C allele display hemoglobin levels that are higher than those in individuals with two copies of the T allele (Scheinfeldt et al 2012). Recent research also has identified HIF pathway candidate genes showing signatures of natural selection in other human populations, including Sherpa, Indians, and Mongolians (Aggarwal et al 2010;Hanaoka et al 2012;Kang et al 2013;Xing et al 2013;Jeong et al 2014).…”
Section: Andean and Ethiopian Adaptation To High Altitude And Geneticmentioning
confidence: 99%